Conducting a psychosocial and lifestyle assessment as part of an integrated care approach for childhood obesity: experiences, needs and wishes of Dutch healthcare professionals - L. W. Koetsier; M. M. A. van Mil; M. M. A. Eilander; E. van den Eynde; C. A. Baan; J. C. Seidell; J. Halberstadt (BMC, 2021)
Abstract Background The causes and consequences of childhood obesity are complex and multifaceted. Therefore, an integrated care approach is required to address weight-related issues and improve children's health, societal participation and quality of life. Conducting a psychosocial and lifestyle assessment is an essential part of an integrated care approach. The aim of this study was to explore the experiences, needs and wishes of healthcare professionals with respect to carrying out a psychosocial and lifestyle assessment of childhood obesity. Methods Fourteen semi-structured interviews were conducted with Dutch healthcare professionals, who are responsible for coordinating the support and care for children with obesity (coordinating professionals, 'CPs'). The following topics were addressed in our interviews with these professionals: CPs' experiences of both using childhood obesity assessment tools and their content, and CPs' needs and wishes related to content, circumstances and required competences. The interviews comprised open-ended questions and were recorded and transcribed verbatim. The data was analysed using template analyses and complemented with open coding in MAXQDA. Results Most CPs experienced both developing a trusting relationship with the children and their parents, as well as establishing the right tone when engaging in weight-related conversations as important. CPs indicated that visual materials were helpful in such conversations. All CPs used a supporting assessment tool to conduct the psychosocial and lifestyle assessment but they also indicated that a more optimal tool was desirable. They recognized the need for specific attributes that helped them to carry out these assessments, namely: sufficient knowledge about the complexity of obesity; having an affinity with obesity-related issues; their experience as a CP; using conversational techniques, such as solution-focused counselling and motivational interviewing; peer-to-peer coaching; and finally, maintaining an open-minded, non-stigmatizing stance and harmonizing their attitude with that of the child and their parents. Conclusions Alongside the need for a suitable tool for conducting a psychosocial and lifestyle assessment, CPs expressed the need for requisite knowledge, skills and attitudes. Further developing a supporting assessment tool is necessary in order to facilitate CPs and thereby improve the support and care for children with obesity and their families.